Untangling interactions of a zinc(ii) complex containing a coumarin–porphyrin unit with alkaloids in water solutions: a photophysical study. Issue 4 (26th January 2015) - Santos, Carla I. M.; Oliveira, Elisabete; Santos, Hugo M.; Menezes, José C. J. M. D. S.; Faustino, M. Amparo F.; Cavaleiro, José A. S.; Capelo, J. L.; P. M. S. Neves, Maria da Graça; Lodeiro, Carlos
Abstract : A metal complex1 derivative from a coumarin bearing a porphyrin unit is sensitive to the alkaloids caffeine2, nicotine3 and cotinine4 in solution and/or in the gas phase. Abstract : A metal complex1 derivative from a coumarin bearing a porphyrin unit was spectroscopically characterized and its sensing ability towards the alkaloids caffeine2, nicotine3 and cotinine4 was evaluated in these studies. This probe shows to be sensitive to the alkaloids studied, where a detectable amount of 2.5 ± 0.3 μM of cotinine was determined in dam water from the Vigia Dam located in the Montoito village region, Alentejo district, Portugal. The interaction of1 with cotinine was also verified by MALDI-TOF-MS, where it was found with peaks at 877.2 and 1053.3 m / z corresponding to the species [1 H] + and [1 CotinineH] +, respectively.